Association between Trauma-Induced Vertebral Fractures and Motor Weakness in Patients with Diffuse Idiopathic Skeletal Hyperostosis - Muhammad Saqib, Tauseef Raza, Usman Akmal, Ahmed Waqas, Arif Kaleem, Mian Iftikhar Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An age-related disorder known as diffuse idiopathic skeletal hyperostosis (DISH) causes aberrant ossification of ligaments, joint capsules, and other soft tissues. Objective: The purpose of this study was to examine the frequency and features of diffuse idiopathic skeletal hyperostosis (DISH) in patients hospitalized to our hospital due to vertebral fractures. Methods: The study comprised 115 patients who had just been diagnosed with a vertebral fracture. Radiographs, CT scans, and MRIs were used to confirm a recent spinal fracture and to determine whether DISH was present. We also compared patients with and without DISH based on age, sex, blood test results, treatment, duration of hospital stay, and bone mineral density. Results: The patients mean age was 68.9 years. Among all, 42 (36.5%) cases were diagnosed with diffuse idiopathic skeletal hyperostosis (DISH), in which majority were males. There was a significant age difference between the patients in the DISH and non-DISH groups (P = 0.007), as well as higher levels of glycated hemoglobin A1c (P< 0.005), bone mineral density (P<0.004), and length of hospital stay (P< 0.001) in the DISH group compared to the non-DISH group. Conclusion: The percentage of patients with DISH among those who suffered from vertebral fractures in our study was 36.5%. Patients with DISH need to be closely monitored because they might need various treatments. Keywords: DISH, CT scans, Hospital stay.